rpoB Targeted Loop-Mediated Isothermal Amplification (LAMP) Assay for Consensus Detection of Mycobacteria Associated With Pulmonary Infections - Grandjean Lapierre, Simon; Drancourt, Michel (Frontiers in Medicine, 2018)
Loop-mediated isothermal amplification (LAMP) is a nucleic acid method which has been used to identify mycobacteria including Mycobacterium tuberculosis in clinical microbiology laboratory and point of care settings. Previously published LAMP protocols for detection of mycobacterial species used conventional specific primer and targeted the 16S rRNA, gyrB, and insertion sequence genes. We developed and evaluated a LAMP assay targeting a mycobacterial rpoB gene conserved sequence and incorporating degenerate primers. This assay allowed consensus detection of mycobacterial species from pure culture, clinical respiratory tract samples, and mycobacteria growth indicator tube (MGIT) liquid-based culture medium. A panel of twenty mycobacterial species were successfully detected at detection thresholds of 102 CFU/mL and 103 CFU/mL when respectively performed on pure culture suspension or sputum and MGIT broth. The inclusion of degenerate bases in LAMP primers increased the diversity of mycobacterial species identified by the assay without negatively affecting analytical sensitivity. LAMP-based consensus detection of multiple pathogens can be achieved with degenerate primers therefore allowing the design of rapid multi-disease screening assays. Despite high analytical sensitivity, species specificity and the advantageous operational characteristics of LAMP over PCR, challenges such as potential ambiguity in visual interpretation of results and occasional non-specific amplification precludes the implementation of novel LAMP assay in routine diagnostics both in centralized and point-of-care laboratory.